A Nova História Cultural - Moura, Denise A. Soares de (Revista de História, 1995)
HUNT, Lynn. A Nova História Cultural. Trad. Jefferson Luis Camargo. São Paulo, Martins Fontes, 1992 (O Homem e a História).